THE MULTIFUNCTIONALITY OF CHILD-CENTRED EDUCATIONAL ENVIRONMENT IN THE UPBRINGING CONTEXT - Katane, Irēna; Katans, Edgars; Lietapure, Stella (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Education is a means and also a guarantee for the facilitation of society’s sustainable development. According to the historical age of the development of society, the dominant paradigms for education had set goals, tasks, out of which resulted also educational functions. Within the educational process, including pedagogical process, there are regularities resulting into conclusive pedagogical axiom: the more human-friendly and meeting his individual needs and interests is educational environment, the more successful is the individual’s all-rounded development in such environment. Nowadays upbringing is an important component of educational process .The aim of theoretical research is to substantiate the multifunctionality of child-centred educational environment in the upbringing context. The authors of the article have substantiated the methodological base of theoretical research as well: humanistic approach and ecological approach, including there has been presented the various aspects of the concept ‘educational environment’.